Cation Engineering by Three‐Dimensional Organic Spacer Cations for Effective Defect Passivation in Perovskite Solar Cells. Issue 12 (14th November 2022) - Shang, Xueni; Zhang, Boxue; Gao, Deyu; Li, Mengjia; Wang, Chenglin; Meng, Fanbin; Chen, Cong
Abstract: Low‐dimensional additive engineering could effectively reduce the high‐density trap defect density and improve the stability of perovskite solar cells (PSCs). To avoid the limiting effect of charge carrier transfer by incorporating the large‐size long alkyl chain organic cations, we developed a new three‐dimensional organic spacer cation, 1, 4‐diazabicyclo [2, 2, 2] octane‐1, 4‐diium (DABCO 2+ ), to passivate the defects and enhance the device stability. DABCO 2+ with fine crystal structure and thermal stability could result in substantially fewer structural defects, enhance carrier lifetime, and inhibit nonradiative recombination loss. Structural analysis of CsFAPbI3 perovskite doped with different concentrations of the three‐dimensional organic spacer cations shows a clear correlation between the structure and the resultant perovskite films. Consequently, DABCO 2+ modified CsFAPbI3 ‐based PSCs could achieve an optimized PCE of 23.02% with high stability exceeding 1500 h. This work opens a new approach to fabricating PSCs with enhanced stability for future commercial applications. Abstract : A new three‐dimensional organic spacer cation, 1, 4‐diazabicyclo [2, 2, 2] octane‐1, 4‐diium (DABCO 2+ ) was developed to passivate defects and enhance the device stability.